Reducing flood risk and improving system resiliency in Sacramento, California: overcoming obstacles and emerging solutions - Pawley, Anitra; Moldoff, David; Brown, Josh; Freed, Stephanie (Frontiers in Water, 2023)
Sacramento, the capital of California, has a population of over 2 million and is one of the most flood prone regions in the nation. Its problems exemplify those of many urban communities built near riverine and deltaic systems, that are subject to climate change. The city and its surrounding communities are protected by an elaborate system of levees and flood bypasses; but aging infrastructure, expected increases in extreme wet weather, and projected sea level rise are increasing the risk of levee failures. We explore how flood management approaches including social/institutional (non-structural), traditional structural, and ecological based approaches are being implemented in the Lower Sacramento/North Delta Region amid significant obstacles, to build resilient flood management systems. We review four case studies, one structural levee project and three multi-benefit projects that are only recently being implemented. We also examine the barriers, constraints, and challenges for implementing flood protection projects, and how project proponents are collectively working through these obstacles. We conclude that significant progress has been made in building flood resiliency since the 2008 Central Valley Flood Protection Act and the release of the 2012 Central Valley Flood Protection Plan. Informational tools and policies are being developed to educate the public and prepare for floods. Structural levee investments are substantial and are being implemented through partnerships. Statewide policies and investments are increasingly supporting multi-benefit projects that incorporate ecological restoration/enhancement while expanding flood volume capacity. Progress on implementing multi-benefit projects has been slow, due to land acquisition, easements, funding, regulatory and construction challenges; however, solutions to these impediments are emerging to facilitate more rapid progress. It is essential to continue and intensify the progress made in the last two decades, by learning from past projects, and improving on existing research to implement sustainable projects at a faster rate.